Meta-analysis of genetic diversity of the VP1 gene among the circulating O, A, and SAT2 serotypes and vaccine strains of FMD virus in Egypt - El Nahas Abeer F. (Journal of Veterinary Research, 2020)
Three strains of the FMD virus (A, O, and SAT 2) were recognised as causes of the FMD circulating in Egypt. The aims of this study were to trace the FMDV isolates from outbreaks in Egypt to understand their epidemiology and evolution and to understand the situation of the vaccine strains compared with the circulating serotypes.